1992
DOI: 10.1111/j.1467-8624.1992.tb01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Influences on the Acquisition and Socialization of Children's Health Attitudes and Behavior: An Integrative Review

Abstract: An overview and synthesis of the literature documenting various influences on the socialization and acquisition of children's health attitudes and behavior is the focus of this review. Cognitive-developmental approaches to understanding children's health attitudes are presented, followed by an exploration of an individual differences perspective on children's acquisition of health attitudes and behavior. The influence of various socialization agents, including families, peers, schools, and the media, on childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 99 publications
0
35
0
1
Order By: Relevance
“…Much of this research has emanated from the literature on family socialization processes (Baranowski & Nader, 1986; Tinsley, 1992) including social cognitive theory (Bandura, 1986). One of the primary concepts in social cognitive theory is observational learning, a process through which individuals evaluate and model the behaviors of others.…”
Section: The Risk Perception Attitude Frameworkmentioning
confidence: 99%
“…Much of this research has emanated from the literature on family socialization processes (Baranowski & Nader, 1986; Tinsley, 1992) including social cognitive theory (Bandura, 1986). One of the primary concepts in social cognitive theory is observational learning, a process through which individuals evaluate and model the behaviors of others.…”
Section: The Risk Perception Attitude Frameworkmentioning
confidence: 99%
“…It has also been suggested that illness is a learning experience for children27 28 and that developmental changes in concepts of illness may be the result of experience rather than stages of cognitive development 29. Children with chronic illnesses have a more sophisticated and mature understanding of illness than well peers 29…”
Section: The Challenge Of Measuring a Child’s Quality Of Lifementioning
confidence: 99%
“…Parents shape both children's health-related behaviors and their food environments (Tinsley, 1992), thus playing a primary role in the development of eating behavior. Costanzo and Woody's (1985) domain-specific obesity proneness model posits that parents who are concerned about their child's obesity proneness may exert more control over eating behavior, potentially through use of restrictive feeding practices and encouragement to diet.…”
Section: Introductionmentioning
confidence: 99%